APPLYING THE VALUE STREAM MAP (VSM) AS AN LEAN TOOL TO INCREASE VALUE ADDED AND ELIMINATE THE INHERENT WEST OF THE PRODUCTION SYSTEM A CASE STUDY AT THE IRAQI DRILLING COMPANY - Asst. Tech. Afrah Oudah Sabeeh; Tech. Suhaila Juma Radi; Prof. Dr. Safaa Mohammed Hadi (Galaxy International Interdisciplinary Research Journal, 2023)
This research discusses the use of Value Stream Map (VSM) as an improvement technique in a case study company in particular to reduce waste, improve process efficiency and quality, and hence improve process performance. The purpose of this research is to use the Value Stream Map (VSM) to identify the waste present in the process and remove it or reduce it by the use of lean tools, activities that did not add any value are eliminated or modified. As a result, value added is increased, the delivery time is reduced to improve the performance of the whole process. This study follows the case study method, during site visits, researchers conducted interviews to gather information. A set of appropriate quantitative methods such as )cycle time, waiting time, changeover time, etc.) were used. The research concluded that VSM can be used in the Iraqi Drilling Company, as it has proven its ability to improve operations performance and thus improve efficiency and productivity.